2015
DOI: 10.1039/c4cs00163j
|View full text |Cite
|
Sign up to set email alerts
|

Lab on upconversion nanoparticles: optical properties and applications engineering via designed nanostructure

Abstract: Over the past decade, high-quality lanthanide doped upconverting nanoparticles (UCNPs) have been successfully synthesized with the rapid development of nanotechnology. Due to the unique electron configuration of lanthanide ions, there are rich energy level structures in the near-infrared, visible and ultraviolet spectral range. However, for UCNPs, only a limited number of efficient upconversion excitation and emission have been generated due to the limited number of sensitizer (Yb(3+)) and activator (Tm(3+), E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
326
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 550 publications
(338 citation statements)
references
References 267 publications
1
326
0
4
Order By: Relevance
“…31 Thus, lanthanidebased upconversion nanoparticles (UCNPs) have special optical characteristics, such as sharp emission lines, large anti-Stokes shifts of several hundred nanometers, and the absence of autofluorescence in biosamples. [32][33][34][35][36][37][38] Therefore, UCNPs have been recently used as building blocks in the construction of multimodal contrast agents for imagingguided therapy. [39][40][41][42][43][44][45] In the current study, upconversion nanoparticles (UCNPs) were first prepared by a typical solvothermal method.…”
Section: Xing Et Almentioning
confidence: 99%
“…31 Thus, lanthanidebased upconversion nanoparticles (UCNPs) have special optical characteristics, such as sharp emission lines, large anti-Stokes shifts of several hundred nanometers, and the absence of autofluorescence in biosamples. [32][33][34][35][36][37][38] Therefore, UCNPs have been recently used as building blocks in the construction of multimodal contrast agents for imagingguided therapy. [39][40][41][42][43][44][45] In the current study, upconversion nanoparticles (UCNPs) were first prepared by a typical solvothermal method.…”
Section: Xing Et Almentioning
confidence: 99%
“…Because of the fast exploration of UCNPs, several reviews have already summarized the preparation and applications of UCNPs 23, 37, 38, 39, 40, 41, 42, 43, 44, 45. In this review, we mainly focus on recent achievements on the usage of lanthanide‐doped UCNPs as efficient probes for biodetection since 2014.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the dopant of rare metals may improve the sensitive performance of nanomaterials [16]. For instance, Li et al have reported that the sensitivity of Er-doped SnO 2 nanobelt device is 9 to the formaldehyde gas [17].…”
Section: Introductionmentioning
confidence: 99%